PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA KOPERASI SIMPAN PINJAM DAN PEMBIAYAAN SYARIAH TUNAS ARTHA MANDIRI SYARIAH WILAYAH WONOGIRI - Santoso, Andik Dwi; Kurniawati, Ony; Adi, Titok Waskito (STIE Mahardhika, 2025)
Two key elements that might cause a drop in employee performance are a lack of accountability in completing tasks and an unsupportive work environment. The purpose of this study is to investigate how much employee performance at the Tunas Artha Mandiri Syariah Savings and Loans Cooperative in the Wonogiri district is influenced by work environment and work discipline. A sample of 35 respondents participated in the survey. Multiple linear regression analysis and SPSS processing were used to examine the collected data. The study revealed that employee performance (Y) is significantly impacted by the work discipline variable (X1). This suggests that superior performance is displayed by employees with higher levels of discipline. Additionally, it was demonstrated that the work environment variable (X2) had a considerable impact on employee performance (Y). This implies that a welcoming and comfortable workplace will increase worker productivity. Employee performance is concurrently influenced by the work environment and work discipline. These findings give the business a solid foundation on which to build strategic policies that prioritize enhancing discipline and overseeing a more encouraging workplace in order to maximize employee performance.